PENGARUH SISTEM PEMUNGUTAN PAJAK KENDARAAN BERMOTOR (PKB) MELALUI LAYANAN DRIVE THRU, SAMSAT KELILING, DAN E-SAMSAT TERHADAP KEPATUHAN WAJIB PAJAK - Riza Frycilia Sofia Afidah (STKIP NU Kabupaten Tegal, 2022)
This study aims to determine and examine the effect of the motor vehicle tax collection system (PKB) through drive thru services, mobile samsat, E-samsat on the compliance of two-wheeled motorized vehicle taxpayers in the samsat of Surakarta. The research method used in this study is a quantitative method. The data used is primary data obtained through the distribution of questionnaires to the taxpayers of two-wheeled motorized vehicles in the Surakarta City Samsat. The sampling method used accidental sampling with random sampling technique. The number of samples in this study were 138 respondents. Testing the hypothesis in this study using multiple linear regression analysis using the SPSS version 20 program. The results of this study indicate that the drive thru variable has no significant effect on motor vehicle taxpayer compliance. While the mobile samsat and E-samsat variables have a significant effect on motor vehicle taxpayer compliance.